Factors Related to Primary Dysmenorrhoea in Students at The Faculty of Medicine of Andalas University in 2023 - Dzaky, Aditya Luthfian; Karmia, Hudila Rifa; Abdiana, Abdiana (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: Dysmenorrhoea or menstrual pain is a commonly reported reproductive health issue, particularly affecting those aged 18-25 years. It can significantly disrupt daily activities and reduce productivity. The high prevalence of dysmenorrhoea is attributed to multiple factors, which are multifactorial in nature. The research aims to identify the factors related to incidence of primary dysmenorrhoea among in students of the Bachelor of Medical Education Study Program at the Faculty of Medicine, Andalas University 2023. Method: A cross-sectional study was conducted in October 2023 using a Google form to collect primary data. The sample consisted of 212 female students from the batch of 2020-2022, selected using a simple random sampling technique. Univariate and bivariate analyses were used to analyse the data, with the chi-square test employed in bivariate analysis. Results: The results of the study of the relationship between age of menarche, family history of sleep quality, and duration of menstrual bleeding, the incidence of primary dysmenorrhoea obtained p values of p = 0.538, p = 0.059, p = 0.004, and p = 1.000. Conclusion: There is a significant relationship between sleep quality and the incidence of primary dysmenorrhoea. However, there is no significant relationship between menarche age, family history, and duration of menstrual bleeding with the incidence of primary dysmenorrhoea in students of the Bachelor of Medical Education Study Program at the Faculty of Medicine, Andalas University 2023.It is important for all women of childbearing age to be aware of the risk factors that cause dysmenorrhoea and the measures taken to alleviate menstrual pain.